Frequency and Identification of Risk Factors of Uveitis in Juvenile Idiopathic Arthritis: A Long-term Follow-up Study in a Cohort of Italian Children. Issue 7 (October 2020) - Conti, Giovanni; Chirico, Valeria; Porcaro, Federica; Fede, Claudia; Vitale, Agata; Fede, Antonio; Castagna, Irene; Fede, Carmelo
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease of childhood. The JIA–associated uveitis represents the most common extra-articular manifestation. Objectives: The main aim of this study was to evaluate frequency and risk factors of uveitis in a pediatric population affected by JIA. Methods: One hundred eight Italian children with JIA were followed during a follow-up period of 13 years. Association between uveitis, antinuclear antibodies (ANAs), and subtype of arthritis has been estimated, and Kaplan-Meier curves were generated to assess the probability of ocular complications during the follow-up period. Results: Twenty-one patients developed uveitis, after 96.5 ± 50.4 months from the enrollment. According to JIA subtypes, the oligoarthritis subtype was characterized by the highest prevalence (39%) of uveitis. The greatest risk of uveitis has been detected in oligoarthritis patients associated to ANA positivity (risk ratio, 8.6; 95% confidence interval, 2.27–32.9; χ 2 = 20.4), whereas the worst evolution was revealed in patients with oligoarthritis and high levels of ANAs, with a progression time of 36 months (log-rank χ 2 = 16.39; p < 0.0001; risk ratio, 18; 95% confidence interval, 7.3–44.2). Conclusions: Patients with early-onset ANA-positive oligoarticular JIA have the highest risk of developing uveitis. A routine ophthalmological follow-up is required at regular intervals, even though the joint disease is clinically quiescent.